Regulation of Tumor Necrosis Factor-α by Peptide Lv in Bone Marrow Macrophages and Synovium - Mukai, Manabu; Uchida, Kentaro; Okubo, Tadashi; Takano, Shotaro; Matsumoto, Toshihide; Satoh, Masashi; Inoue, Gen; Takaso, Masashi (Frontiers in Medicine, 2021)
Background: Bone marrow-derived monocyte/macrophages are recruited into synovial tissue, where they contribute to synovial inflammation in osteoarthritis through inflammatory cytokine production. Recent studies have suggested that V-Set and Transmembrane Domain-containing 4 (VSTM4) and its fragment, peptide Lv, exhibit immunosuppressive activity on T cells and vascular endothelial growth factor (VEGF)-like activity, respectively. Given that evidence suggests that VEGF may play a role in macrophage function, we investigated peptide Lv-mediated regulation of inflammatory cytokines in bone marrow macrophages (BMM) and synovial inflammation. Method: To investigate the effects of peptide Lv, BMM were stimulate with vehicle, LPS, or LPS + peptide Lv, and Tnfa, Il1b, Il6, and Ifng expression were evaluated using quantitative PCR (qPCR). TNF-α and IFN-ꝩ production were measured using ELISA. To examine the effect of peptide Lv deficiency on macrophages and synovitis, peptide Lv-deficient mice were generated using genome editing. LPS-induced Tnfa and Ifng expression and TNF-α and IFN-ꝩ production were evaluated in BMM isolated from wildtype and peptide Lv-deficient mice. Additionally, Tnfa and Ifng expression levels were compared between wildtype and peptide Lv-deficient mice before and after knee injury. Results: Peptide Lv suppressed the LPS-mediated elevation in TNF-α and IFN-g. LPS stimulation significantly increased TNF-α and IFN-ꝩ production in BMM derived from peptide Lv-deficient mice compared to wildtype mice. Synovial TNF-α expression in the injured knee was elevated in peptide Lv-deficient compared to wildtype mice. Conclusion: Peptide Lv suppressed TNF-α in macrophages and plays a role in synovial inflammation. Thus, peptide Lv may be a useful therapeutic target for synovitis.